Autosomal dominant GDAP1 mutation with severe phenotype and respiratory involvement: A case report - Rodriguez-Hernandez, Adrian; Mayo, Meagan; Jauregui, Lilibeth; Patel, Pooja (Frontiers in Neurology, 2022)
Charcot Marie Tooth (CMT) is a heterogeneous group of genetic disorders characterized by progressive motor and sensory neuropathy. CMT is a multi-gene disorder with several possible mutations responsible for a wide range of clinical presentations. A specific mutation of the ganglioside-induced-differentiation-associated protein 1 (GDAP1) gene is associated with the axonal subtype of CMT (CMT2K) which is inherited in an autosomal dominant fashion, as well as the demyelinating subtype (CMT4A) which is inherited in an autosomal recessive pattern. Phenotypic disease expression is largely dependent on these inheritance patterns. While the autosomal recessive form (CMT4A) exhibits severe disease with an early onset, the autosomal dominant variant (CMT2K) tends to have milder phenotypes and a later onset. We describe an atypical presentation of a patient with severe CMT2K with rapidly progressive polyneuropathy, respiratory failure, and dysphonia. We suggest that this case will inspire further evaluation of disease heterogeneity and variants.